Gary Becker's Impact on Economics and Policy - Lazear, Edward P. (American Economic Review, 2015)
Gary Becker was one of the greatest thinkers of the 20th century. He advanced social science by introducing economic thinking into areas that were thought to be off limits. Because his theory was motivated by his desire to explain the world, his analyses were highly policy relevant. His work on discrimination, deterrence of crime, fertility, human capital, and the family all produced implications that were testable and verified by his and others' empirical research. Equally important, each research area provided policy guidance and many of his ideas have been implemented by government and non-government organizations.